Minocycline Ameliorates Depressive-Like Behavior and Demyelination Induced by Transient Global Cerebral Ischemia by Inhibiting Microglial Activation - Du, Bingying; Li, Hailong; Zheng, Huiwen; Fan, Cunxiu; Liang, Meng; Lian, Yongjie; Wei, Zelan; Zhang, Yanbo; Bi, Xiaoying (Frontiers in Pharmacology, 2019)
Global cerebral ischemia (GCI) commonly occurs in the elderly. Subcortical white matter lesion and oligodendrocyte (OLG) loss caused by cerebral ischemia have been implicated in post-ischemic depression and cognitive impairment. OLGs are necessary for axonal myelination; the disrupted differentiation of oligodendrocyte progenitor cells (OPCs) is associated with impaired remyelination. Evidence has indicated that increased levels of inflammatory cytokines released from activated microglia induce depression-like behavior by affecting neurotransmitter pathways, but the mechanisms remain elusive. We explored the potential mechanisms that link microglia activation with GCI-induced depression and cognitive dysfunction by studying effects of minocycline on white matter damage, cytokine levels and the monoaminergic neurotransmitters. An acute GCI animal model was generated through bilateral common carotid artery occlusion to induce ischemic inflammation and subcortical white matter damage. Minocycline, an inhibitor of microglia activation, was intraperitoneally administrated immediately after surgery and continued daily for additional six days. Minocycline shortened the immobile duration in tail suspension test and forced swimming test, while no improvement was found in Morris water maze test. The plasma levels of IL-1β, IL-6, TNF-α, HMGB1 and Netrin-1 were significantly reduced with the treatment of minocycline. Minocycline treatment substantially reversed demyelination in corpus callosum and hippocampus, alleviated hippocampal microglia activation and promoted OPCs maturation, while no effect was found on hippocampal neurodegeneration. Besides, the content of dopamine (DA) in the hippocampus was upregulated by minocycline treatment after GCI. Collectively, our data demonstrated that minocycline had an anti-depressant effect by inhibiting microglia activation, promoting OPCs maturation and remyelination. Increased DA in hippocampus may also play a role in ameliorating depressive behavior with minocycline treatment.